ANALISIS KEMAMPUAN BERPIKIR DEDUKSI HIPOTESIS TERHADAP PEMAHAMAN KONSEP RANGKAIAN RESISTOR PADA LISTRIK ARUS SEARAH - Hidayah, Nevy Nurul; Wiyanto, Wiyanto; Sopyan, Achmad (Physics Communication, 2017)
The development of technology needed humans that qualified and high in order thinking. Hyphotetical deductive thinking is one of high order thinking. It is appeared on students of senior high school in Tambakboyo by their scientific research. Result of observation physics teachers RPP still used to talkative methode. Understanding abstract concepts need laboratory activity to formed thinking student. This study aims to know correlation between hyphotetical deductive thinking and concepts understanding, profile of thinking and concept understanding. The subjects was selected using saturated sampling. Design of study using sequential explanatory. There is positive correlation between hyphotetical deductive thinking and concept understanding. Correlation category on XI IPA is medium and strong. Correlation both of them was influenced by another factors like the difficulty of students and trouble in lack of time when do hyphotetical deductive test and direct current resistive electrical circuits test is easy because this subject was learned in X class. Profiles thinking in XI IPA is dominant on transition and hyphotetical deductive thinking. Profiles of concepts understanding by XI IPA on good and good enough category.